Antioxidant activity, ascorbic acid, phenolic compounds and sugars of wild and commercial Tuberaria lignosa samples: effects of drying and oral preparation methods. - Pinela, José (2013)
The antioxidant activity and phytochemical composition (ascorbic acid, free sugars and phenolic compounds) of decoctions and infusions of wild and commercial samples of Tuberaria lignosa (Sweet) Samp. (Fam. Cistaceae) aerial parts were evaluated and compared. Among wild samples, the effects of the drying method (freeze or shade-drying) on those parameters were studied. Infusion of the freeze-dried wild sample gave the highest levels of sugars, while infusion of shade-dried wild sample and decoction of the freeze-dried sample presented higher ascorbic acid and phenolic compounds content (including ellagitanins and flavonoids) than the other samples. The last two samples also revealed higher antioxidant activity and, in some cases, even higher than trolox. Decoctions gave lower amounts of disaccharides than infusions, which seemed to be hydrolyzed increasing the content in monosaccharides in the first samples. Commercial samples showed the lowest content in phenolic compounds, mainly in ellagitanins and flavonoids, as also the lowest antioxidant activity. This work gives scientific evidences to the traditional medicinal uses of wild Tuberaria lignosa, highlighting the interest of its decoctions and infusions as bioactive compounds source and functional beverages.